Placental vascular tree at sea level - Martina, M. (2015)
Objective: To determine the morphology and weight of the placental vascular tree. Material and Methods: Twenty seven placentas were collected from normal pregnant women who had prenatal care at Clinica Villa Maria–EsSalud. Patients who had diabetes mellitus, arterial hypertension, preeclampsia, nephropathy, Rh isoimmunization and anemia were not included. The specimens were rinsed with tap water for 30 minutes, the fetal membranes were trimmed off at the level of its insertion. The placentas were weighed and the umbilical vessels were catheterized and flushed with 100 mL of normal saline solution and then the acrylic solution (15 mL of liquid with 7,5 of powder) was injected. The placentas were immersed in hot water for 30 minutes then fixed in 10% formaldehyde for two hours and finally immersed in hydrochloric acid for 7 days in order to obtain the acrylic cast of the placental vascular tree by corrosion. Results: The mean weight of the vascular tree was 16,9 g (8,7-25,3 g). The mean placental ratio was 0,1571 (0,1081-0,1944) and the mean placental vascular ratio was 0,0317 (0,0230-0,0560); in addition there was a direct relation between the weight of the placenta and the weight of the vascular tree. Conclusions: Our data will permit comparison with high altitude placentae, where hypoxia could modify placental vascular tree.